Napjatostní a pevnostní analýza rámu jízdního kola a stanovení poddajnosti ve vybraných místech konstrukce. - Prášil, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Cílem této práce bylo provést napěťově deformační analýzu konstrukce rámu jízdního kola za přístupů prosté pružnosti. Musel jsem nejdříve toto úlohu převést z prostorové úlohy na rovinnou a dále zjednodušit tak, aby splňovala prutové předpoklady. V této práci jsem se hlavně zaměřil na statickou bezpečnost konstrukce. Bezpečnost jsem vypočítal pro dva zatěžovací módy. První, když cyklista jede bez šlapání a druhý, když cyklista jede do kopce ve stoje. Při výpočtech jsem použil matematických softwarů jako je Mathcad 14 či Maple 12 ale také modelovacích softwarů především Autocad, pro určení přesných vzdáleností. Matematickou analýzu jsem zkontroloval s výsledky z programu ANSYS.

Purpose of this work was the realization of stress and strenght analysis of the bike frame with the help of the basic elasticity approach. At first I had to transfer this task from three-dimensional to two-dimensional and also to simplify to fulfill the beam conditions. I also focused on static safety of the construction. This static safety was solved for two loading modes. First one was define as the load, which cyclist can induce, when he is going on the direct road. Second one was defined as the load, which he can induce, when he is going up to the hill. I used for these calculations mathematical software such as Mathcad 14 or Maple 12, but also modeling software especially Autocad for establishing correct dimensions. At the end I checked the stress and strain analysis obtained by the basic elasticity approach with the solution performed making use of the ANSYS software code.
Stress and strength analysis of the bike frame and compliance assessment at selected construction places.
Keywords: Napěťová analýza; deformace; prostá pružnost; rám kola; bezpečnost; prutová soustava; síla; moment.; Stress analysis; deformation; basic elasticity; bike frame; safety; beam system; force; torque.